Management of Welfare and Job-Security of Employees for Sustainability of Colleges of Education in Nigeria - Ngozi Ibelegbu, Anthonia; Abanyam, Friday Ekahe; Nwachukwu, Chinwendu; J. Garba, Hannatu (Manunggal Halim Jaya, 2023)
This investigation examined ways of improving management of welfare and security of human resources for sustainability of public colleges of education in South-East Nigeria. Two specific purposes and two null hypotheses were used to carry out the study. It adopted descriptive survey research design. The study involved a population of 486 senior administrators in the study area. All the 486 senior administrative officers were involved in the study; since it was of a manageable size there was no sampling in the study. A structured, 35-item questionnaire which was validated by three lecturers was used to collect data for the study. Cronbach Alpha reliability technique was used to ascertain the reliability of the instrument; and it yielded reliability coefficients of 0.76 and 0.84 respectively for the two clusters. Data collection was carried out with the help of seven research assistants. From 486 copies of the questionnaire administered, 462 copies representing 95.1% were correctly answered and returned. The collected data were analyzed with mean and analysis of variance (ANOVA) at 0.05 level of significance. From the data collected and analyzed, the study identified 16 ways of improving management of welfare and 19 ways of improving management job security of human resources for sustainability of public colleges of education in southeast Nigeria. The mean ratings of participants did not show any significant difference on ways of improving management of welfare and job security of human resources for sustainability of public colleges of education in southeast Nigeria. The study among others advanced that colleges of education’s management team should establish staff welfare and job security programmes that are helpful and appropriate to emerging trends in work places.